'Choreographed by the angels'? Ireland and the centenary of the First World War. (2nd October 2017) - Pennell, Catriona
Abstract : The centenary of the First World War in Ireland is just one event amongst a broader series of commemorations collectively known as the decade of centenaries. This context, in itself, is unique in comparison to the other national case studies reviewed in this special edition. While the First World War centenary in Ireland is certainly no sideshow, it does have to share its place under the commemorative spotlight with other, arguably more important (at least to a large section of the population), events in Irish history. After contextualising the difficult journey the First World War has traversed in achieving recognition as part of Ireland's national story, this article seeks to explore the way Ireland has marked the centenary of the First World War between 2014 and 2016. A range of examples led by government (whether in the Republic, Northern Ireland or the UK) and community groups (broadly defined) across the north and south of the island of Ireland will be examined in order to consider how, from a set of different perspectives, the centenary has been approached so far in Ireland. How have Irish publics been engaged with the First World War over the course of the centenary so far? What is being emphasised in these commemorative activities; what is being left out? What meaning is being drawn from the war at the centenary moment and for what present-day political purposes?